Acute treatment of migraine with external trigeminal nerve stimulation: A pilot trial. (18th February 2019) - Kuruvilla, Deena; Mann, Joseph I; Schoenen, Jean; Penning, Sophie
Objective: The main objective of this study was to obtain efficacy data for external trigeminal nerve stimulation (e-TNS) in the acute treatment of migraine in patients using the device at home. Methods: This was a single-center, open-label trial conducted at the Rochester Clinical Research Center (Rochester, NY, USA). Patients who met International Classification of Headache Disorders, Third Edition, criteria for migraine with and without aura for ≥1 year and having between 2 and 8 moderate or severe attacks per month were recruited. Patients were advised to treat one migraine attack of moderate to severe intensity that started less than 4 h earlier and was not treated with an acute migraine medication, with a 2-h e-TNS session. Primary outcome measures were pain freedom at 2 h and most bothersome migraine-associated symptom (MBS) freedom at 2 h. Secondary outcome measures were pain relief at 2 h, the absence of migraine-associated symptoms at 2 h, the use of rescue medication between 2 and 24 h, and sustained pain freedom at 24 h. Results: Fifty-nine subjects were included in the study, and among them, 48 subjects were eligible for the modified intention-to-treat analysis. After 2 h of e-TNS, 35.4% of the subjects were pain-free, 60.4% were MBS-free, 70.8% had pain relief, and 45.8% were free from all migraine-associated symptoms. Half of the subjects took rescue medication between 2 h and 24 h, and sustained pain freedom at 24 h was achieved for 25.0% of the subjects. Regarding safety, 15 patients reported adverse events, all minor and fully reversible, mainly forehead paresthesia. Conclusions: This study shows that e-TNS with the Cefaly® Acute Device is effective, well-tolerated, and safe for the acute treatment of migraine in patients using the device at home. A large, multicenter, randomized, sham-controlled trial is needed to confirm this finding.